2009
DOI: 10.1152/ajprenal.90710.2008
|View full text |Cite
|
Sign up to set email alerts
|

Marinobufagenin induces increases in procollagen expression in a process involving protein kinase C and Fli-1: implications for uremic cardiomyopathy

Abstract: The cardiotonic steroid marinobufagenin (MBG) has been implicated in the pathogenesis of experimental uremic cardiomyopathy, which is characterized by progressive cardiac fibrosis. We examined whether the transcription factor Friend leukemia integration-1 (Fli-1) might be involved in this process. Fli-1-knockdown mice demonstrated greater cardiac collagen-1 expression and fibrosis compared with wild-type mice; both developed increased cardiac collagen expression and fibrosis after 5/6 nephrectomy. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(167 citation statements)
references
References 20 publications
2
162
1
2
Order By: Relevance
“…Fli-1 might be involved in this process. Fli-1-knockdown mice demonstrated greater cardiac collagen-1 expression and fibrosis compared with wild-type mice (Elkareh et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Fli-1 might be involved in this process. Fli-1-knockdown mice demonstrated greater cardiac collagen-1 expression and fibrosis compared with wild-type mice (Elkareh et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…MBG was seen to induce decreases in Fli-1 expression in cardiac and renal fibroblasts, which was dependent on the nuclear translocation of PKC delta from the cytoplasm. This translocation seems to be necessary for the phosphorylation and degradation of the Fli-1 (Elkareh, Periyasamy et al 2009). This is illustrated in figure 3.…”
Section: Uremic Cardiomyopathymentioning
confidence: 97%
“…T h i s p r o b a b l y is the explanation for how the signal transduction is eventually terminated. (Tian, Liu et al 2003;Liu, Liang et al 2005;Yuan, Cai et al 2005;Pierre, Yang et al 2007;Chen, Cai et al 2008;Elkareh, Periyasamy et al 2009). This signaling pathway may link to Bricker's concept of CTS as a natriuretic hormone.…”
Section: Signaling Though the Sodium Pumpmentioning
confidence: 99%
“…Studies have found that MBG activated pre-fibrotic signal, which could activate various signaling pathways and EGFR signals by inhibiting NKA, leaded to degeneration of the left ventricular muscle fli-1 and inducing collagen -1 synthesis (Elkareh et al, 2009;Liu et al, 2012;Xie et al, 2013). Study found myocardial fibrosis and siginificant elevation of MBG level in rats with a minipump for infusing MBG and rats had uremia myocarditis (Elkareh et al, 2007).…”
Section: Marinobufagenin and Fibrosismentioning
confidence: 99%
“…Although in the short term, the effect of MBG might balance the high salt load and slow the elevation of blood pressure (Mou et al, 2014), the vasoconstrictive effected by inhibiting NKA may be the long-term response of MBG. In addition, Dietary sodium restriction did not reduce level of plasma MBG (Jablonski et al, 2013).Studies have found that MBG activated pre-fibrotic signal, which could activate various signaling pathways and EGFR signals by inhibiting NKA, leaded to degeneration of the left ventricular muscle fli-1 and inducing collagen -1 synthesis (Elkareh et al, 2009;Liu et al, 2012;Xie et al, 2013). Study found myocardial fibrosis and siginificant elevation of MBG level in rats with a minipump for infusing MBG and rats had uremia myocarditis (Elkareh et al, 2007).…”
mentioning
confidence: 97%